Development Of A Library Information System Based On Web At State Vocational School I Lobalain - Fando, Alessandro Fijai; Manu, Gerlan A.; Enstein, Jhon (JUPE : Jurnal Pendidikan Mandala, 2025)
This thesis discusses the Development of a Web-Based Library Information System. This type of research is research and development (R&D) using the Waterfall system development model with five stages, namely: analysis, design, implementation, testing, maintenance. The research discusses 2 important objectives in this research, namely producing a web-based library information system and describing the feasibility of a web-based library information system at SMK Negeri 1 Lobalain. The development process in this research produced a web-based library information system with a display consisting of 7 main menus, namely Location/Shelf, Category, Publisher, Books, Loans, Returns and Members. Meanwhile, the feasibility test for a web-based library information system can be proven by data from validation results from media experts I, II and validation by I librarians, which can be seen with a final score of 84.9% with a very good feasibility level and the results of product validation questionnaires from students with a final score. 90.68% of eligibility qualifications are very good, no need for revision so it can be concluded that the web-based library information system is very effective, efficient and easy to operate and according to the results of the questionnaire the web-based library information system is suitable for use in the library processing process at SMK Negeri 1 Lobalain